Bloodletting cupping combined with conventional measures therapy for psoriasis: A systematic review and meta-analysis of randomized controlled trials - Ma, Xiaoyu; Li, Dilong; Zhao, Minghui; He, Jiaming; Yang, Fan; Kong, Jingyan (Frontiers in Medicine, 2023)
Background: Psoriasis is an immune-mediated inflammatory disease prone to recurrence. Some studies indicated that bloodletting cupping combined with conventional measures therapy had been proposed as a treatment strategy for psoriasis. Therefore, we did a systematic review and meta-analysis to assess the effectiveness of this combination therapy in reducing the severity of disease in patients with psoriasis. Methods: The articles were searched for the following electronic databases from January 1, 2000, to March 1, 2022: PUBMED, EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL), Chinese Biomedical Literature Database (CBM), Chinese Scientific Journal Database (VIP database), Wan-Fang Database and China National Knowledge Infrastructure (CNKI). No language restrictions. The quality of articles was evaluated using the Rev Man 5.4 software (provided by the Cochrane Collaboration), comparing bloodletting cupping combined with conventional measures therapy to conventional measures treatments. The studies obtained randomized controlled trials (RCTs) of bloodletting cupping combined with conventional standard treatment for treating psoriasis. Two trained researchers (Xiaoyu Ma and Jiaming He) independently reviewed the literature; extracted data based on exclusion and inclusion criteria, and assessed the quality of the included studies. We estimated the aggregate data using a random effects model. Findings: We identified 164 studies. 10 studies met the inclusion criteria for the meta-analysis. The primary outcome indicator was the total number of effective individuals. Secondary outcomes included the PASI (Psoriasis Area and Severity Index), adverse effects and the DLQI (Dermatology Life Quality Index). Compared with conventional treatments, bloodletting cupping combined with conventional medicine yielded an improved total effective number of persons (RR=1.15, 95%CI: 1.07 to 1.22, P<0.00001), PASI (MD=-1.11, 95%CI: -1.40 to -0.82, P<0.00001), and DLQI score (MD=-0.99, 95%CI: -1.40 to -0.59, P<0.0001). We found no significant difference in adverse reactions (RR=0.93, 95%CI: 0.46 to 1.90, P=0.85). The heterogeneity test showed the total effective numbers (P<0.00001, I2 =43%), PASI (P<0.00001, I2 =44%), and DLQI scores (P<0.00001, I2 =0%). Interpretation: Bloodletting cupping combined with conventional treatment can achieve the ideal treatment for psoriasis. However, the combined treatment in psoriasis needs to be further evaluated in high-quality RCTs with large sample sizes to enable future studies in clinical use.